Pengaruh Harga, Kualitas Produk Dan Kepercayaan Pelanggan Terhadap Loyalitas Pelanggan - Hariyono, Iskak; Ruspitasari, Widi Dewi; Handoko, Yunus (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2023)
Health is an important part of everyone's primary needs. PT. Setia Andalan Sukses has an important role in the distribution chain of quality medical devices in assisting the right diagnosis for patients in need. The purpose of this research is to know and analyze: (1) the effect of price on customer loyalty in PT. Setia Andalan Sukses, (2) the effect of product quality on customer loyalty in PT. Setia Andalan Sukses, and (3) the influence of customer trust in customer loyalty PT. Setia Andalan Sukses, and (4) influence of price, product quality and customer trust simultaneously on customer loyalty in PT. Setia Andalan Sukses. This research was conducted using a quantitative approach to customers PT. Setia Andalan Sukses, namely hospitals located in East Java which have made purchases more than twice in the year 2021. Respondent population 55 Hospital using purposive sampling method. The data obtained were analyzed using research instrument testing and research hypothesis testing using multiple liner regression analysis. The research results show that (1) price has a significant effect on customer loyalty (2) product quality has a significant effect on customer loyalty , (3) customer trust has a significant effect on customer loyalty, and (4) simultaneously price, product quality and customer trust have a significant effect on customer loyalty in PT. Setia Andalan Sukses